Enhanced Evanescent Field Coupling of Smart Particles in Tubular Optical Microcavity for Sensing Application. Issue 4 (17th December 2021) - Yang, Shuo; Wang, Yunqi; Kong, Ye; Huang, Gaoshan; Zhao, Zhe; Wang, Yang; Xu, Borui; Cui, Jizhai; Mei, Yongfeng
Abstract: Whispering‐gallery mode (WGM) optical microcavity with enhanced evanescent field is one of the most perfect systems to study light–matter interaction. Unique sensing devices and potential applications with excellent performance can be expected by integrating smart particles into the microcavity, such as small mode volume and high sensitivity. Here, it is demonstrated that rolled‐up tubular optical microcavity decorated with palladium (Pd) nanoparticles (NPs) is capable for hydrogen (H2 ) sensing. Such microtube with subwavelength wall thickness exhibits enhanced sensing performance, e.g., detection limit of 1000 parts per million (ppm) and sensitivity in the order of 10 −5  nm ppm −1, due to strong coupling in the evanescent field. Experiments and simulations are compared and guided the optimization for high figures of merit. The approach proves a unique route to couple smart particles with rolled‐up WGM microcavity for gas sensing, which have great application potentials in the field of nanophotonics and smart sensors. Abstract : Smart Pd particles are integrated into thin‐wall tubular whispering‐gallery mode microcavity with enhanced evanescent field for high‐performance H2 sensing application. Experiments and simulations are adopted to study the ideal wall thickness for high figure of merit. This work provides a unique way to achieve environmental sensing via evanescent field coupling between microcavity and smart material.